The Role Of Start-Ups In Driving Global Economic Growth - Nurbina; Imaduddin; Ramlawati (Nomico, 2025)
This study aims to analyse the role of start-ups in driving global economic growth using a quantitative approach. Start-ups, as innovative business actors, are considered capable of increasing productivity, creating new employment opportunities, and accelerating the adoption of digital technology, all of which have a positive impact on national economies. The research also examines the role of venture capital as a crucial funding source that supports the development of start-ups, as well as the influence of digitalisation as a key driver in market expansion and operational efficiency. Moreover, this study explores the differences in start-up contributions between developed and developing countries, which are influenced by infrastructure, policy frameworks, and the quality of human resources. The findings reveal that a supportive ecosystem—such as government policies and the availability of capital—is essential to maximise the contribution of start-ups towards inclusive and sustainable economic growth. This research provides strategic recommendations for policymakers to strengthen the start-up ecosystem in order to face global economic competition.